Intersectionality of Gender, Social Class, and War Trauma in the Middle East : A Multilayer Analysis - Helsa Nasution; M. Agung Rahmadi; Luthfiah Mawar; Nurzahara Sihombing (Calory Journal Medical Laboratory Journal, 2025)
This multilayer meta-analysis investigates the intersectionality between gender, social class, and war-related trauma in the Middle East through a systematic review of 87 studies (N = 31,459) published between 2000 and 2023. Analytical findings reveal a strong and significant correlation between gender and trauma severity (r = 0.67, p < 0.001), with women experiencing a 2.8 times higher prevalence of PTSD compared to men. Furthermore, results from hierarchical regression demonstrate that social class functions as a substantial moderator (β = 0.45, p < 0.001), with individuals from lower social class backgrounds exhibiting a 3.2 times greater risk of trauma. Further structural path analysis reveals the presence of dual mediation (CFI = 0.96, RMSEA = 0.04), with access to mental health services and social support serving as primary mediators (indirect effect = 0.38, 95% CI [0.29, 0.47]). These results expand the contributions of Al-Krenawi and Graham (2012) and Mangrio et al. (2019) by illustrating the complex interaction of the three dimensions (Gender, Social Class, and War Trauma), which had previously been examined only separately. In addition, this study identifies a new pattern termed the "spiral trauma effect," a mechanism wherein the intersectionality of gender, social class, and trauma mutually reinforce each other in a recurring cycle (effect size d = 0.89), thereby deepening the understanding of trauma dynamics in conflict zones across the Middle East. Finally, the predictive model developed in this research demonstrated an accuracy rate of 84.3% in identifying high-risk individuals. Thus, these results are considered to provide an innovative framework for the development of empirically-based trauma interventions in Middle Eastern war zones.